Math, asked by 987614, 11 months ago

plz! solve the 2 questions...!
if it will be correct

> I will follow you
> thanks your 5 answer
> mark u as brainlist
------------------------------------
> wrong answer will reported
>spam answer will deleted​

Attachments:

Answers

Answered by TakenName
4

\frac{3t-2}{4} - \frac{2t+3}{3} =\frac{2}{3} -t

→ Multiplication

12\times\frac{3t-2}{4} -12\times \frac{2t+3}{3} =12\times\frac{2}{3} -12t

3(3t-2)-4(2t+3)=8-12t

→ Distribution Law

9t-6-8t-12=8-12t

13t=26

→ Division

t=2

The point of these questions is using basic laws of calculations.

We use +, -, ×, ÷ to solve algebra questions. I hope you can solve question 20 yourself.

Answered by Anonymous
5

Answer:

1 → t = 2

2 → x = -1

hope it's help you...!!

Similar questions